Eruption Characteristic of the Sleeping Volcano, Sinabung, North Sumatera, Indonesia, and SMS Gateway for Disaster Early Warning System - Sari Bahagiarti Kusumayudha; Puji Lestari; Eko Teguh Paripurno (Faculty of Geography, Universitas Gadjah Mada, 2018)
Sinabung, the sleeping volcano since the year 1600 awakened and erupted in 2010, 2013, and 2015. The volcano is located in Karo District, North Sumatera Province, Indonesia, geographically on 3o10’ North Latitude, and 98o23, East Longitude. It is about 2460 m high above sea level, and the highest volcano of Sumatera. Sinabung has been estimated about 400 years long inactive, therefore categorized as B type of volcano. It was astonishing; Sinabung erupted on 27 August 2010, again on November 2013, and in May to June 2015. Awakening of the volcano hypothetically has been triggered by last decade earthquakes happened in North Sumatera and surrounding area, including the great earthquake and tsunami of Aceh, December 2004 that caused about 115,000 people died. Because of the volcano has been slept for a long time, people live in the surrounding area were not prepared yet to facing the eruption. In order to reduce the risk such a countermeasure should be developed especially that directly involving local people participation. In this case such an environmental communication system is needed to be developed, it is SMS gate way for disaster early warning system.